Parish politics, urban spaces and women's voices in seventeenth century Norwich (Chapter 9) - WILLIAMSON, Fiona (Institutional Knowledge at Singapore Management University, 2018)
This chapter explores defamation and spaces of interaction. It argues that although much research has been completed on women's words in urban social settings, it is important to consider how women's words influenced the politics of the parish, governing the twist and turns of men's, and women's lives according to the patriarchal ideals that dictated appropriate behaviours and ways of living. The chapter explores the spaces of parish politics, those places that can be considered central to the interactions and social relationships of urban dwellers, places that included the streets, domestic thresholds and the church. The Frogg and Austin case study demonstrates how inhabitants constructed a personal frame of reference and thought about the world around them, viewing the city as a series of parishes. The chapter interprets parish social relations as not only reflecting notions of honour, morality or gender, but as broader expressions of what it meant to belong to a community and contemporary senses of urban space.